DAYA TARIK HUTAN KOTA PULAU BUNGIN DESA KOTO TALUK KUANTAN - Ningsih, Mirna Fitria; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The City Forest of Pulau Bungin has untapped tourism potential that has not been well-documented. This research aims to determine the Attractions, Amenities, Accessibility, and Ancillary aspects of the City Forest of Pulau Bungin in the village of Koto Taluk Kuantan. The study employs a qualitative method with a descriptive qualitative approach to depict and explain the existing conditions by collecting data and information in the field. In this research, data collection techniques include interviews, observations, and documentation. Based on the research findings, it can be concluded that the facilities available in the City Forest of Pulau Bungin are inadequate, with some facilities being poorly maintained due to insufficient facility management and a lack of cleanliness maintenance by the operators, such as the Traditional Sugar Mill, Toilet, Gazebo, Parking Area, Trash Bin, and Bridge. Keywords: Attractiveness, City Forest